DIGITALIZATION OF PUBLIC ADMINISTRATION AS A FACTOR OF DIGITAL TRANSFORMATION OF UKRAINE - KOVAL, Yana; KUCHERENKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the 21st century, digitalization has become a key area of society’s development, fundamentally changing the way government institutions, businesses, and citizens interact. This process is particularly relevant for countries with transformational economies, such as Ukraine, where digital technologies are not only a tool for modernization but also a means of overcoming systemic challenges in public administration. At the same time, the digitalization of the public sector is accompanied by a number of problems, ranging from regulatory uncertainty and the digital divide to staff shortages and information insecurity. The article examines the digitalization of public administration as a key factor in the digital transformation of modern society, in particular in the context of Ukraine. The author analyzes the impact of the Fourth Industrial Revolution and the widespread use of information and communication technologies (ICT) on the transformation of the public sector. The author focuses on the benefits of digitalization - in particular, transparency, increased management efficiency, and expanded access to services - as well as on the systemic barriers to its implementation. The author discusses the terminological differences in the interpretation of the concepts of “digitalization”, ‘digitalization’ and “informatization”, which complicate the formation of a unified conceptual framework for digital policy. Particular attention is paid to the analysis of the factors that influence the success of digital transformation in the public sector, among which an important role is played by technological infrastructure, the level of digital literacy of civil servants, and a strategic vision of digital development at the level of public policy. The article also provides examples of effective digital practices in Ukraine that demonstrate the potential for large-scale implementation. The role of the state as not only a user, but also an active generator of digital change responsible for creating conditions for digital inclusion is revealed. It is emphasized that the digitalization of public administration has not only an instrumental but also a strategic dimension, as it forms a new paradigm of interaction between the state and citizens based on a service approach, openness, analytics and personalization. It is emphasized that the success of digital transformation directly affects the trust in state institutions, the level of social justice, adaptability to global challenges, and the overall competitiveness of the country in the digital era. Thus, the digitalization of public administration is viewed not only as a technical upgrade, but also as a fundamental change in the logic of the state’s functioning in the information society, which requires an interdisciplinary approach and coordinated actions at all levels of government.